Radiative cooling of size-selected gas phase clusters. Issue 3 (2nd October 2019) - Ferrari, Piero; Janssens, Ewald; Lievens, Peter; Hansen, Klavs
Abstract : Predicted almost forty years ago, the radiation from thermally populated excited electronic states has recently been recognised as an important cooling mechanism in free molecules and clusters. It has presently been observed from both inorganic clusters and carbon-based molecules in molecular beams and ion storage devices. Experiments have demonstrated that many of these systems radiate at rates approaching microsecond time scales, and often with a distinct dependence on the precise number of atoms in the system. The radiation acts as a strongly stabilising factor against both unimolecular decay and thermal electron emission. In astrophysical context, radiative cooling provides a mechanism to dissipate internal energy in star-forming processes, and stabilises molecules selectively in the circumstellar medium. The consequences of an active radiative cooling channel for nanoparticle production will likewise favour special sizes in non-equilibrium formation processes. In this review, the radiative cooling of clusters is presented and illustrated with examples of experiments performed on small carbon, metal, and semiconductor clusters, and on PAH molecules. The experimental and theoretical techniques used are discussed, together with the consequences of radiative cooling on size-to-size stability patterns of clusters.